The Effect of Motivational Interviewing on Adolescent Risk Behaviors: A Literature Review - Retno Wulandari, Eka; Lindayani, Linlin; Herdiman, Herdiman (KnE Life Sciences, 2022)
Motivational interviewing is a client-centered counseling method that is used to promote behavior change by eliciting client motivations for change and analyzing conflicting client motivations. The purpose of this literature review was to summarize the effect of motivational interviewing on adolescent risk behaviors. Articles published in English between 2015-2020 were searched in MEDLINE, CINAHL, and the Cochrane Library. The reviewers extracted and summarized the data using the Joanna Briggs Institute ( JBI) data extraction tool. A total of six articles were included in this review. It can be concluded from the results that counseling combined with motivational interviewing is beneficial at reducing risky sexual behavior in teenagers and in preventing HIV transmission. Keywords: adolescent, motivational interviewing, risk behaviors, review